Analisis Dampak Kinerja Pengelolaan Zakat Dalam Pengentasan Kemiskinan Pada Kabupaten Ogan Komering Ilir - Ghufron Khafidin, Muhammad; Firdaus, Achmad; Mukhlish Yusuf, Ahmad (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
The population of Ogan Komering Ilir Regency in 2020 was 769,348 people. The poverty rate in 2020 reached 123.34 thousand people, then in 2021 it increased to 124.78 thousand people. The increasing poverty rate is a problem for the performance of zakat managers, while zakat itself is a form of poverty alleviation effort. This research is to determine the impact of zakat management performance in alleviating poverty in Ogan Komering Ilir district and the factors that influence the performance of zakat management in poverty alleviation. Quantitative descriptive analysis method. The total respondents in this study were 100 respondents from zakat management employees in each district, sub-district, sub-district/village of Ogan Komering Ilir district. In this research, a new variable is added in the performance of zakat management, namely the muzakki trust variable. The analysis method in this research uses Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this research show that zakat management performance factors influence poverty alleviation by 59.2% and the remaining 40.8% is influenced by other variables. Overall, the performance of zakat management has a positive and significant effect on poverty alleviation.